Hydropneumothorax in Children: A Rare Complication of a Bacterial Pneumonia - Carolina Ortega; Carla Gonzales; Manuel E. Soto-Martinez; Adriana Yock-Corrales (Case Reports in Pediatrics)
Hydropneumothorax is an uncommon presentation of a complicated pneumonia, and very few cases in the pediatric population have been reported. This is a case of a 5-month-old patient who presented to the emergency department (ED) with a three-day history of fever, diarrhea, and respiratory distress. His initial assessment suggested a lower respiratory tract infection and because of his respiratory distress and hypoxia a chest X-ray was performed. Other clinical information and radiologic studies will be discussed further, but his chest X-ray suggested a right-sided hydropneumothorax secondary to a complicated pneumonia. He completed 12 days of IV antibiotic treatment and required a chest tube for drainage. Patient was discharged home with a full recovery.